An Interdisciplinary Review on The Culture of Sacred Time in The Context of Social Learning - Saadet İder (Türkiye Din Eğitimi Araştırmaları Dergisi)
The coexistence of religion and culture emerges in folk beliefs at sacred times. Sacred times play a mediating role between God and his believers. The endeavour to access the Sacred Being results in the productivity of human beings and cultural heritage. Religious references on sacred time are associated with the behaviours of people and enable the emergence of many cultural elements. The representation of the Sacred over time creates "the culture of sacred time" unique to each society. Cultural practices in different forms at sacred times contribute to the acquisition of religious feelings and behaviours in religious education. The study aims to reveal the contribution of the culture of sacred time to the development of behaviour through social learning in religious education. Since the phenomenon of sacred time is a common problem in folklore and religious sciences, the study is carried out by interdisciplinary approach. The method of the study is systematic literature review on the resources of both disciplines. The study reveals the contribution of the culture of sacred time to the development of religious behaviours through Bandura's social learning theory and Vygotsky's cognitive development theory.